Anti-Saccharomyces cerevisiae Antibodies in Acute Myocardial Infarction. (1st December 2007) - Cinemre, Hakan; Bilir, Cemil; Gokosmanoglu, Feyzi; Kadakal, Figen
Abstract : Background: Elevated anti- Saccharomyces cerevisiae antibody (ASCA) immunoglobulin (IgG) and IgA levels were first described in the serum of Crohn disease patients and have increasingly been reported in other inflammatory diseases. The role of in situ and remote inflammation in atherosclerosis is a major area of interest. In this study, we compared ASCA IgG and IgA levels in acute myocardial infarction (AMI) and controls to investigate the possible role of ASCA in AMI. Methods: Serum samples were obtained from 140 consecutive patients who presented to the emergency department with acute chest pain. AMI was diagnosed by electrocardiography and serial enzymes. Patients ruled out for acute coronary event were grouped as controls. ASCA IgA and IgG levels were determined using enzyme-linked immunosorbent assay. Groups were compared for statistically significant difference. Results: ASCA IgG titers ranged between 0.1 and 31.0 RIU/mL (mean 4.92) in the AMI group and 0.1 and 6.0 (mean 0.84) in the controls. The groups were found to differ very significantly ( p = .001). ASCA IgA titers ranged between 2.0 and 200.0 RIU/mL (mean 13.73) in the AMI group and 2.0 and 11.5 RIU/mL, (mean 4.25) in controls. The groups differed significantly ( p = .32). AMI and controls were also analyzed for ASCA IgA and IgG positivity. Both groups differed significantly from controls ( p = .013). Conclusion: Elevated ASCA IgA and IgG levels as well as ASCA positivity in the AMI might suggest use of ASCA as a marker for atherosclerotic plaque instability. It might also provide a link between inflammatory processes and increased cardiovascular risk. Further studies are needed on a Saccharomyces cerevisiae -based diet, related intestinal colonization, and associated inflammation, autoimmune disorders, and cardiovascular events.